2021
DOI: 10.3389/fgene.2021.638708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Microgravity on the Proteome and Secretome of the Polyextremotolerant Black Fungus Knufia chersonesos

Abstract: Black fungi are a group of melanotic microfungi characterized by remarkable polyextremotolerance. Due to a broad ecological plasticity and adaptations at the cellular level, it is predicted that they may survive in a variety of extreme environments, including harsh niches on Earth and Mars, and in outer space. However, the molecular mechanisms aiding survival, especially in space, are yet to be fully elucidated. Based on these premises, the rock-inhabiting black fungus Knufia chersonesos (Wt) and its non-melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 122 publications
1
12
0
Order By: Relevance
“…Observed, alterations in proteins involved in carbohydrate metabolism upon exposure to space conditions stay in agreement with previous studies of A. niger JSC-093350089 ( Romsdahl et al, 2018 ), and other filamentous fungi, including Aspergillus fumigatus ( Blachowicz et al, 2019a , b ) and A. nidulans ( Romsdahl et al, 2019 ). Similarly, a black fungus Knufia chersonesos exposed to low-shear simulated microgravity (LSSMG) also exhibited differential expression of proteins involved in carbohydrate metabolism ( Tesei et al, 2021 ). On the other hand, a yeast, Candida albicans, exposed to spaceflight environment on the “SJ-10” satellite for 12 days showed decreased abundance of proteins involved in carbon metabolism, suggesting that yeast and filamentous fungi differ in adaptive responses to space environment ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Observed, alterations in proteins involved in carbohydrate metabolism upon exposure to space conditions stay in agreement with previous studies of A. niger JSC-093350089 ( Romsdahl et al, 2018 ), and other filamentous fungi, including Aspergillus fumigatus ( Blachowicz et al, 2019a , b ) and A. nidulans ( Romsdahl et al, 2019 ). Similarly, a black fungus Knufia chersonesos exposed to low-shear simulated microgravity (LSSMG) also exhibited differential expression of proteins involved in carbohydrate metabolism ( Tesei et al, 2021 ). On the other hand, a yeast, Candida albicans, exposed to spaceflight environment on the “SJ-10” satellite for 12 days showed decreased abundance of proteins involved in carbon metabolism, suggesting that yeast and filamentous fungi differ in adaptive responses to space environment ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies with submerged liquid cultures of A. niger under low-shear modeled microgravity in the High Aspect Ratio Vessel (HARV), at a slow-rotation of 25 rpm, found no significant changes in spore germination, mycelium growth or cell wall integrity (Sathishkumar et al, 2014). Interestingly, further HARV studies at 30 rpm with the black fungus Knufia chersonesos found that low-shear modeled microgravity induced changes in the regulation of the DHN-melanin biosynthesis pathway (Tesei et al, 2021). Another study also reported that A. niger growth was not inhibited in a 3-D clinostat (Yamazaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MG is defined as a state of weightlessness that occurs due to decreased physical force exerted by gravity, where gravity ranges from 10 –3 to 10 –6 g (Bijlani et al 2020). There is general agreement that MG is a crucial factor influencing microbial physiology in the space capsule during flight missions ( Tesei et al 2021 ). Due to technological and logistical hurdles, the microbial experiments under true MG in space stations are minimal.…”
Section: Introductionmentioning
confidence: 99%